Volodymyr Pilat - the creator and leader of the Fighting Hopak style. Contribution to the modern history of Ukrainian martial arts - Wojciech J. Cynarski (Jan Długosz University in Częstochowa, 2023)
Many nations today promote their historical martial arts and combat sports. This may result from the need to emphasize their own national traditions and cultural heritage. Thanks to outstanding figures, enthusiasts and people with a sense of mission, traditions that are partly lost are being created or restored. An example is Grand Master Volodymyr Pilat - the creator of the system called Boiovyi hopak (Battle / Combat hopak). The author, based on a direct interview and available publications, presents his path to the creation of this martial art, which is also a combat sport, and the establishment of an international federation, which indicates an already advanced institutional development. An analysis of sources was also used, including film materials and photos (visual anthropology). The specificity of this fighting art is shown, which is strongly related to the experiences of of Master Pilat's "way of the warrior". Boiovyi hopak was created on the basis of Cossack traditions and the experience of Volodymyr Pilat's "way of the warrior". The historical hopak was a dance. It is often practised with music. Among the traditional weapons there are a long stick, sabre, pike, scythe, sickle, mace, flail and ice axe.